Implementasi Teknik Arsir Dalam Mengembangkan Kreativitas Menggambar Pada Anak Usia 5-6 Tahun di RA ZU Tsaqif - Silvia Anggraini; Sri Wahyuni; Fakih Hakim (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
This study aims to see the implementation of shading techniques in developing drawing creativity in children aged 5-6 years at RA Zu Tsaqif. The method used in this study is a qualitative descriptive method. The population in this study is 15 children. The data collection techniques used are observation, interviews and documentation. The instrument used is an observation sheet. The data analysis techniques used are data reduction, data presentation and conclusion. The result of this study is that the creativity of drawing AUD in RA Zu Tsaqif began to develop as expected, but not as much as possible because many children are busy with their own activities, some are lazy, and some say tired. The implementation of shading techniques in developing children's drawing creativity requires many facilities and infrastructure that must be equipped to improve the teaching and learning process.